2014
DOI: 10.1002/stem.1603
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26 Family Is Required for Human Adipogenesis and Drives Characteristics of Brown Adipocytes

Abstract: Adipose tissue contains thermogenic adipocytes (i.e., brown and brite/beige) that oxidize nutrients at exceptionally high rates via nonshivering thermogenesis. Its recent discovery in adult humans has opened up new avenues to fight obesity and related disorders such as diabetes. Here, we identified miR-26a and -26b as key regulators of human white and brite adipocyte differentiation. Both microRNAs are upregulated in early adipogenesis, and their inhibition prevented lipid accumulation while their overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
146
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 76 publications
4
146
0
2
Order By: Relevance
“…Increases in myomiR-1 and other miRNAs, including miR-455 and -26, were highly correlated with BA-specific proteins in differentiating BAs in the present and previous studies. 27,37 For instance, expression profiles of miR-1/206 and miR-133 were highly correlated with the MEF2C protein during myogenesis, 38,39 and the upregulated MEF2C in turn initiated expression of miR-1 at early stage of myogenesis by binding to the intragenic of miR-1-2 cluster. 39 miR-1 and -133 were often generated together from 2 bicistronic clusters but execute opposite functions during the Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in myomiR-1 and other miRNAs, including miR-455 and -26, were highly correlated with BA-specific proteins in differentiating BAs in the present and previous studies. 27,37 For instance, expression profiles of miR-1/206 and miR-133 were highly correlated with the MEF2C protein during myogenesis, 38,39 and the upregulated MEF2C in turn initiated expression of miR-1 at early stage of myogenesis by binding to the intragenic of miR-1-2 cluster. 39 miR-1 and -133 were often generated together from 2 bicistronic clusters but execute opposite functions during the Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been reported that the miR-26 family are involved in human adipogenesis. 49 , 22 More importantly, the miR-26a/b are expressed concomitantly with their host genes in GMEC. Our data revealed a functional significance between miR-26a/b and the CTDSP family in the regulation of lipid metabolism in GMEC, which is consistent with the effect on human adipogenesis 22 , 48 and in cell cycle control.…”
Section: Discussionmentioning
confidence: 99%
“…49 , 22 More importantly, the miR-26a/b are expressed concomitantly with their host genes in GMEC. Our data revealed a functional significance between miR-26a/b and the CTDSP family in the regulation of lipid metabolism in GMEC, which is consistent with the effect on human adipogenesis 22 , 48 and in cell cycle control. 5 The expression of PPARG is essential for fat cell differentiation and normal lipid metabolism in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs have been found to play important regulatory roles in either promoting (miR-140, miR-26a/b, and miR-455) (11,12) or suppressing (miR-27 and miR-133) adipogenesis (13,14). miR-140 is an important regulator of developmental pathways and stem cell differentiation and is a tumor suppressor in breast cancer (15)(16)(17).…”
mentioning
confidence: 99%